Pseudo-invasive Vasculocentric Adenomyosis- A Diagnostic Dilemma - Akhtar, Kafil; Abrari, Andleeb; Tirkey, Rachel (Asian Pacific Journal of Cancer Biology, 2023)
Pseudo-invasive, vasculocentric adenomyosis is a rare benign lesion of the uterus, characterized by the aberrant, pathological presence of variable sized, non-neoplastic endometrial glands and surrounded by endometrial stroma deep within the myometrial blood vessels. This condition usually affects multiparous women in their fourth and fifth decades, with other risk factors being prior caesarian surgery or uterine surgery. Mostly the patients present with abnormal uterine bleeding, pelvic pain, dysmenorrhea, dyspareunia, or infertility while a third of them may be asymptomatic. Microscopic examination of hysterectomy specimens remains the gold standard to make a definitive diagnosis. Herein we present a rare case of Pseudo-invasive, vasculocentric Adenomyosis in a 47 year old multigravida female, who presented with a history of chronic pelvic pain with menorrhagia, dyspareunia and excessive menstrual bleeding for the past four months, with a history of lower uterine caesarean section a decade ago.